Associations of parity, breast-feeding, and birth control pills with lumbar spine and femoral neck bone densities - Hreshchyshyn, M M; Hopkins, A; Zylstra, S; Anbar, M (American journal of obstetrics and gynecology, 1988)
The relationships between parity, breast-feeding, and the use of birth control pills and the bone densities of the lumbar spine and the femoral neck, measured by dual-photon densitometry, were studied in normal women. Femoral neck density was found to decrease by 1.1% per live-birth, whereas lumbar spine density showed no significant association with parity. Breast-feeding was found to increase lumbar spine density by 1.5% per breast-fed child, whereas femoral neck density was not significantly correlated. No significant relationships between the use of birth control pills and the bone densities were found.